Modelling of the test of the JT-60SA HTS current leads. (July 2017) - Zappatore, A; Heller, R; Savoldi, L; Zanino, R
Highlights: The metal shells surrounding the KIT current leads included in 1D code CURLEAD. CURLEAD shell-conductor contact resistance calibrated in one steady-state test. Computation shows very good agreement with experiments in different conditions. Abstract: The CURLEAD code, which was developed at the Karlsruhe Institute of Technology (KIT), implements an integrated 1D transient model of a high temperature superconducting (HTS) current lead (CL) including the room termination (RT), the meander-flow type heat exchanger (HX), and the HTS module. CURLEAD was successfully used for the design of the 70 kA ITER demonstrator and of the W7-X and JT-60SA CLs. Recently the code was successfully applied to the prediction and analysis of steady state operation of the ITER correction coils (CC) HTS CL. Here the steady state and pulsed operation of the JT-60SA HTS CLs are analysed, which requires also the modelling of the HX shell and of the vacuum shell, which was not present in the ITER CC. The CURLEAD model extension is presented and the capability of the new version of CURLEAD to reproduce the transient experimental data of the JT-60SA HTS CL is shown. The results obtained provide a better understanding of key parameters of the CL, among which the temperature evolution at the HX-HTS interface, the GHe mass flow rate needed in the HX to achieve the target temperature at that location and the heat load at the cold end.